2014
DOI: 10.1155/2014/816524
|View full text |Cite
|
Sign up to set email alerts
|

Personality Pathology Predicts Outcomes in a Treatment-Seeking Sample with Bipolar I Disorder

Abstract: We conducted a secondary analysis of data from a clinical trial to explore the relationship between degree of personality disorder (PD) pathology (i.e., number of subthreshold and threshold PD symptoms) and mood and functioning outcomes in Bipolar I Disorder (BD-I). Ninety-two participants completed baseline mood and functioning assessments and then underwent 4 months of treatment for an index manic, mixed, or depressed phase acute episode. Additional assessments occurred over a 28-month follow-up period. PD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…However, although Wenze et al. found that the degree of personality disorder pathology predicted depressive symptoms, they did not find an association with functional impairment. Loftus et al.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, although Wenze et al. found that the degree of personality disorder pathology predicted depressive symptoms, they did not find an association with functional impairment. Loftus et al.…”
Section: Discussionmentioning
confidence: 89%
“…Studies have revealed that co-occurring personality disorder features in patients with BD predict a worse outcome (50). However, although Wenze et al (51) found that the degree of personality disorder pathology predicted depressive symptoms, they did not find an association with functional impairment. Loftus et al (52) also observed comorbid personality disorder to be associated with impaired functioning but this relationship was not independent of mood symptoms in multivariate analysis.…”
Section: Predictors Of Being Granted a Disability Pensionmentioning
confidence: 98%